Influence of Some Plasma Fatty Acids on the Phospholipid Fatty Acid Pattern of Human Platelets – An “Ex Vivo” Experience - Vallés, Juana; Aznar, Justo; Santos, M Teresa (Thrombosis and Haemostasis, 1984)
Some correlations between plasma and platelet fatty acids (FA) were evaluated “ex vivo” in 94 normal subjects.The highest relationships between total FA from plasma and platelets were found for 18:1 (r = 0.74) and 18:2 (r = 0.67). Low correlations were obtained for free fatty acids (FFA). The most significant correlations between fatty acids esterifying plasma and platelet phospholipids were found for the 18:1 (r = 0.66); 18:2 (r = 0.74) and 20:5 (r = 0.66).Our results suggest that the platelet phospholipid FA could be more easily modified by plasma variation in the FA composition of phospholipids than by variations in the plasma FA composition of the FFA fraction. In addition, the incorporation of FA from plasma into the platelet phospholipids “in vivo” may take place through an acylation-deacylation process and also by the incorporation of whole plasma phospholipid molecules into the platelets, probably through an exchange of plasma lipoproteins and platelets. Finally, arachidonic acid seems to have a different and selective way of incorporation into platelet phospholipids.
Keywords: Platelets; Fatty acids; Phospholipids; Plasma fatty acids